2016
DOI: 10.1093/jmammal/gyw026
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, distribution, and predictive occurrence modeling of Palmer’s chipmunk (Tamias palmeri): a high-elevation small mammal endemic to the Spring Mountains in southern Nevada, USA

Abstract: Although montane sky islands surrounded by desert scrub and shrub steppe comprise a large part of the biological diversity of the Basin and Range Province of southwestern North America, comprehensive ecological and population demographic studies for high-elevation small mammals within these areas are rare. Here, we examine the ecology and population parameters of the Palmer’s chipmunk (Tamias palmeri) in the Spring Mountains of southern Nevada, and present a predictive GIS-based distribution and probability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Further, T . palmeri— endemic to the Spring Mountains in southern Nevada—has predicted constraints to lower slopes, near water sources, and within conifer forests above 2400m, and due to physiological constraints, high temperatures may force this species into higher elevations [ 55 ]. Rubidge et al (2010) found that one chipmunk species, T .…”
Section: Discussionmentioning
confidence: 99%
“…Further, T . palmeri— endemic to the Spring Mountains in southern Nevada—has predicted constraints to lower slopes, near water sources, and within conifer forests above 2400m, and due to physiological constraints, high temperatures may force this species into higher elevations [ 55 ]. Rubidge et al (2010) found that one chipmunk species, T .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies evaluated microhabitat selection (i.e., third-order selection) in the eastern chipmunk ( T. striatus — Geier and Best 1980 ), the Colorado chipmunk ( N. quadrivittatus — Rivieccio et al 2003 ), and Palmer’s chipmunk ( N. palmeri ) and the Panamint chipmunk ( N. panamintinus — Lowrey and Longshore 2013 ). Three studies evaluated habitat selection at the landscape scale (i.e., first-order selection) in N. panamintinus ( Lowrey et al 2016 ) and a subspecies of the Colorado chipmunk, the Oscura Mountains Colorado chipmunk ( N. q. oscuraensis — Perkins-Taylor and Frey 2018 , 2020 ). It is possible that mammalogists have a misunderstanding about the habitat needs of many North American chipmunk species because of the lack of habitat selection studies and complete absence of multiscale habitat selection studies.…”
mentioning
confidence: 99%